Being Jehovah’s Witnesses: Living in the World Without Being Part of It - Di Marzio, Raffaella (The journal of CESNUR, 2020)
This paper aims at furnishing some useful interpretative keys to understand, on the one hand, the decision to become Jehovah’s Witnesses and, on the other, the consolidation of this choice through identification with an organization that stands in a unique position within society. The chosen reference framework is the multi-disciplinary model, which Lewis Rambo and others developed to study the conversion/affiliation process, within the reference framework of the psychology of religion. Through bibliographical research, it was possible to single out studies that explore these converts’ characteristics and the kind of relationship-identification that forms between each member of Jehovah’s Witnesses and the religion they have affiliated with. Differently from what some have argued, becoming Jehovah’s Witnesses does not mean to “isolate” oneself or oppose the world, but rather to relate to the world as evangelizers, who aim to motivate those “on the outside” to share their doctrine, intended as a possible way to salvation for anyone who accepts it.